Design Game Design "Introduction of National Hero Figures For Children” - Renaldi Febriansyah; Rani Hermita (Jurnal Indonesia Sosial Sains, 2024)
This research aims to design an attention-grabbing and educational design game about National Hero Figures, Hero Figures including in history lessons where now history is a compulsory subject that needs to be studied by all children. By studying history, it is hoped that students can know history and appreciate the services of previous heroes and draw subjects from the values contained in it. Through history, values and social skills can be developed for students in the form of democratic values, nationalism, patriotism, responsibility, independence and the importance of education for the progress of a nation. On the other hand, games for children are able to accelerate the occurrence of myelination which can improve cognitive and motor skills and can provoke interest in learning. Researchers designed educational games accompanied by interesting audio, animation and graphics to increase interest and help children learn to get to know national heroes. This design game was designed using Luther Sutopo's multimedia method. The luther sutopo multimedia method consists of several stages, namely concept, design, material collecting, assembly, testing, and distribution. The results obtained in the assessment through a questionnaire that has been tested at Mis Azrina, Jalan Marelan Raya No. 287 B, Rengas Pulau, Kec. in learning to get to know national hero figures that have been proven in the results of the pre-test and post-test.